Alien Sounds - Chiara Meluzzi (RiCognizioni, 2022)
Klingon, a ConLang created for the Star Trek franchise in 1984 by the linguist Marc Okrand, is the subject of this study, which analyzes both its phonology and lexicon. The requirement to sound 'alien,' at least to English mother-speakers, is the major aspect of Klingon phonology: many sounds in its phonological inventory are thus highly unusual and seldom encountered entirely in other languages. Particularly, we will focus on the voiceless alveolar lateral affricate /tɬ/, transcribed as <tlh> and characterizing Klingon phonology starting with the name of the language itself. The article analyzes the distribution of /tɬ/ in Klingon lexicon, by identifying phonological restrictions and possible pattern of sound change.